Promoting EU values in international agreements - Eva, JANČÍKOVÁ; Janka, PÁSZTOROVÁ (Juridical Tribune, 2021)
Within the framework of external relations policy as a subject of international law, the European Union has the right to negotiate, conclude, amend and terminate international agreements on its own behalf, i.e., it has competences granted on it in this area by the Treaties. International agreements concluded at European level are results of an agreement between parties and belong to the sources of European Union Law. Current practice inconcluding international agreements at the level of the European Union proves that trade and investment agreements contain provisions concerning civil society, labor relations and environment. The scientific study opens a discussion on a new model of international agreements which, in addition to trade relations, contain provisions on the social status of employees of the parties and on sustainable development. This new model of international treaties is supported by all Member States. The systems analysis shows that the European Union no longer acts as an economic-integration grouping towards third countries, but as an international organization that takes into account high level of environmental protectionand the protection of employees' industrial relations.